The Association Between the Central Sensitisation Inventory and Temporomandibular Disorders Is Confounded by Migraine, Depression, Widespread Pain and Parafunction. A Cross-Sectional Telehealth Study - Calixtre, Letícia Bojikian [UNESP]; van der Meer, Hedwig Aleida; Visscher, Corine Mirjam; de Oliveira, Ana Beatriz; de Godoi Gonçalves, Daniela Aparecida [UNESP] (Wiley, 2024)
Background: Temporomandibular disorders (TMDs) are conditions that involve the temporomandibular joints, masticatory muscles, and associated tissues, causing orofacial pain. Central sensitisation (CS) is a relevant part of the TMD pathophysiology. Migraine, psychological aspects, parafunctional oral habits and widespread pain are commonly associated with both TMD and CS and could confound the association between them. Objectives: To investigate the association between painful TMD and the Central Sensitisation Inventory (CSI) score, and to assess the presence of confounders in this association. Methods: Cross-sectional study that assessed women with and without orofacial pain complaints using telehealth. The TMD Pain Screener and an online physical examination determined the presence of painful TMD. The following questionnaires were applied: CSI, Headache Screening Questionnaire, Generalized Anxiety Disorder-7, Patient Health Questionnaire-9, Oral Behavior Checklist, Jaw Functional Limitation Scale and the Nordic musculoskeletal questionnaire. A single regression investigated the association between the CSI score and TMD, and a multiple regression investigated the effect of the other outcomes as possible confounders. Confounding was considered present when the association between TMD and the CSI score changed more than 10% after adding a possible confounder to the regression model. Results: Forty-two women with painful TMD and 53 without TMD were included. There was a significant association between the CSI score and the presence of painful TMD (R2 = 0.639; p < 0.001). This association changed when the following outcomes were added to the model: presence of migraine, symptoms of depression, widespread pain and parafunctional oral habits. Conclusion: The positive association between TMD and the CSI score was confounded by migraine, symptoms of depression, widespread pain and parafunctional oral habits.
Keywords: central sensitisation; orofacial pain; primary headache disorders; telehealth; widespread chronic pain